2019
DOI: 10.1371/journal.pone.0224846
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetically transduced human ES cell-derived neural progenitors and their neuronal progenies: Phenotypic characterization and responses to optical stimulation

Abstract: Optogenetically engineered human neural progenitors (hNPs) are viewed as promising tools in regenerative neuroscience because they allow the testing of the ability of hNPs to integrate within nervous system of an appropriate host not only structurally, but also functionally based on the responses of their differentiated progenies to light. Here, we transduced H9 embryonic stem cell-derived hNPs with a lentivirus harboring human channelrhodopsin (hChR2) and differentiated them into a forebrain lineage. We exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…Inward cation current in Opto‐mGluR6 transduced mRPE cells and BMSCs was induced by optical stimulation (Figure 2G‐I). Previous studies had also revealed that optical stimulation‐induced inward currents in ChR2‐neural stem cells and mouse embryonic stem cells 41−43 44 …”
Section: Discussionmentioning
confidence: 99%
“…Inward cation current in Opto‐mGluR6 transduced mRPE cells and BMSCs was induced by optical stimulation (Figure 2G‐I). Previous studies had also revealed that optical stimulation‐induced inward currents in ChR2‐neural stem cells and mouse embryonic stem cells 41−43 44 …”
Section: Discussionmentioning
confidence: 99%
“…125 Effective integration of these biomolecules to hydrogel matrices is key to provide control on neuronal growth and development. As outlined in Table 2, to incorporate biochemical cues within hydrogels, one approach involves replicating the ECM microenvironment using ECM components, 102,111 while another entails providing bioactive cues like peptides 107,115,126 or soluble molecules 103,127,128 to facilitate cell adhesion and growth, either individually or in combination. 103,126 Therefore, hydrogels incorporating biochemical cues can be classified into ECM-integrating hydrogels, peptide-functioned hydrogels, and soluble molecule-encapsulating hydrogels.…”
Section: Tuneable Properties Of 3d Hydrogel Systemmentioning
confidence: 99%
“…These cells differentiated into GABAergic neurons, exhibited a comprehensive set of neuronal markers, and developed outgrowths and synapses that connected with various brain structures. However, it is worth noting that in vivo photostimulation can yield conflicting results [160]. Various aspects of neurogenesis and optogenetic tools for its stimulation are considered in more detail in the review by Salmina et al, 2021 [161].…”
Section: Application Of Optogenetic Approaches To Stimulate Neurogene...mentioning
confidence: 99%